2020
DOI: 10.1111/codi.15231
|View full text |Cite
|
Sign up to set email alerts
|

Increasing experience of modified two‐stage transanal ileal pouch–anal anastomosis for therapy refractory ulcerative colitis. What have we learned? A retrospective analysis on 75 consecutive cases at a tertiary referral hospital

Abstract: Aim Ileal pouch–anal anastomosis (IPAA) should be delayed to a second stage in patients with ulcerative colitis and prolonged exposure to medical therapy. However, there is still discussion about whether a modified two‐stage approach is preferable to a three‐stage approach. Recently, a transanal approach has been introduced to overcome the well‐known difficulties of laparoscopic pelvic surgery. This paper presents short‐term outcomes of transanal IPAA (Ta‐IPAA) according to a modified two‐stage approach. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Further, diverting ileostomy has also been associated with negative psychological impacts and a poor quality of life before closure [38]. Another emerging advantage of a modified 2-stage approach is the possibility for early salvage in the setting of anastomotic leak [20,36,37]. It is theorized that non-diversion results in earlier leak identification which better allows for trans-anal repair with endosponge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, diverting ileostomy has also been associated with negative psychological impacts and a poor quality of life before closure [38]. Another emerging advantage of a modified 2-stage approach is the possibility for early salvage in the setting of anastomotic leak [20,36,37]. It is theorized that non-diversion results in earlier leak identification which better allows for trans-anal repair with endosponge.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies directly compared 2‐stage and modified 2‐stage procedures and demonstrated a shorter length of stay and no increased risk of anastomotic leak in the modified two stage group [33, 34]. Specifically addressing the question of diverting ileostomy, again the results are conflicting, and as a limitation, studies have often grouped indications and included 1‐stage procedures which are no longer applicable to the UC population [8, 9, 13–20]. Few studies have directly compared delayed construction techniques (modified 2‐stage vs. 3‐stage).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, it appears that taIPAA offers improved visualization and access during the low pelvic dissection, likely lower conversion rates, and similar postoperative and functional outcomes. 45 Despite the theoretical benefit of improving the rectal transection and avoiding multiple stapler firings, there does not appear to be a difference in rates of anastomotic leak, 41,46 though future studies with larger sample sizes are needed to better evaluate this new technique. 45…”
Section: Transanal Ileal Pouch Anal Anastomosismentioning
confidence: 99%